2012
DOI: 10.15381/rivep.v23i1.886
|View full text |Cite
|
Sign up to set email alerts
|

Relación Entre La Condición Corporal Y El Nivel De Infestación Parasitaria en Bovinos a Pastoreo Como Criterio Para El Tratamiento Antihelmíntico Selectivo.

Abstract: RESUMENEl objetivo del trabajo consistió en evaluar la relación entre el nivel de infestación por parásitos tipo estróngilos y la condición corporal en bovinos Criollo Río Limón (n=42), Bos taurus (n=54) y Bos indicus (n=11), pertenecientes a dos fincas ganaderas del Municipio Pedraza, Estado Barinas (Venezuela). Las muestras de heces se analizaron por la técnica cuantitativa de McMaster con solución salina sobresaturada. Se evaluó la condición corporal (CC) con una escala de 1 a 5 (1 = flaco; 5 = obeso) emple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
3
Order By: Relevance
“…Factors such as a less effective immune response to tick antigens and differences in skin thickness and grooming behaviors may contribute to this disparity [ 49 ]. This susceptibility to parasitic infestations underscores the challenge posed by the poor adaptability of B. taurus to tropical environmental conditions characterized by high humidity and temperature [ 50 , 51 , 52 ]. To mitigate these issues, particularly within tropical regions and dairy production systems, adopting crossbred or synthetic breeds known for their heightened resistance to parasite infestations is recommended [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as a less effective immune response to tick antigens and differences in skin thickness and grooming behaviors may contribute to this disparity [ 49 ]. This susceptibility to parasitic infestations underscores the challenge posed by the poor adaptability of B. taurus to tropical environmental conditions characterized by high humidity and temperature [ 50 , 51 , 52 ]. To mitigate these issues, particularly within tropical regions and dairy production systems, adopting crossbred or synthetic breeds known for their heightened resistance to parasite infestations is recommended [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent families in cattle were Trichostrongylidae, Eimeriidae, and Taeniidae. However, in Venezuela, it was reported that the most frequent genera belong to the families Trichostrongylidae, Ancylostomatidae, and Strongylidae (Morales et al, 2012). Likewise, Sun et al (2018) reported that the most prevalent parasites were Haemonchus, Ostertagia and Trichostrongylus, belonging to the Trichostrongylidae family, as well as Oesophagostomum of the Strongyloidae family.…”
Section: Discussionmentioning
confidence: 99%
“…En algunas situaciones se ha estudiado la condición corporal como manifestación del efecto de ciertas enfermedades 9 . Tal criterio no pude extenderse a nuestro estudio, donde la inadecuada condición corporal estuvo asociada a variables alimenticias y nutricionales que afectaron generalizadamente a los bovinos.…”
Section: Discussionunclassified